Diskriminasi Implisit Belanda terhadap Pribumi pada Novel Kepunan Karya Benny Arnas - Rifa Nurafia (Jurnal Bahasa dan Sastra, 2022)
Discrimination which describes a social imbalance that causes action. These actions often lead to the emergence of the oppressed parties. This view often comes from racial differences such as the assumption of the natives and the Dutch in the colonial era. This imbalance gave rise to the discourse of colonialism. One of the images of discrimination that appears in the novel entitled Kepunan by Benny Arnas. The novel tells about the friendship of the character Aku and four children of Dutch concubines, although it looks familiar, it turns out that this friendship gives rise to indirect discrimination biases. The purpose of this study is to describe the discrimination received by natives from the Netherlands. This study uses a qualitative analysis method with a postcolonial approach. The analysis is in the form of a narrative text structure using Robert Stanton's theory and Edward Said's postcolonial literary approach, namely the theory of 'Orientalism'. The results of the study indicate that there are forms of discrimination in terms of thought and culture. This form of discrimination is disguised by the behavior of intimacy or friendship that is accepted by my character as an indigenous figure. This form of discrimination indirectly strengthened the attitude of the Dutch superiority as a colonial party.